Potencjał gospodarczy Afryki Zachodniej: wybrane implikacje z analizy taksonomicznej dla ekspansji gospodarczej - Nawrot, Katarzyna A.; Cieślik, Ewa (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2017)
The article attempts to assess the economic potential of West Africa, using the taxonomic methods, formulate policy recommendations, and identify potential geographic directions of cooperation with the West African countries. It consists of four sections. The first part of the article characterizes the economies of West Africa in terms of their economic potential. The second section presents research methods and data applied in taxonomic analysis. Part three of the article discusses the results of taxonomic analysis. In the last part of the article we attempted to formulate recommendations for the economic policy of European countries and the strategies of European enterprises in stimulating expansion in the West African countries.